EEG response in humans for frequency-tagged anticorrelated random-dot stereograms: Increased coherency and alpha oscillations - Derzsi, Zoltan (Frontiers in Neuroscience, 2022)
In humans, the presence of a neural mechanism triggered by anticorrelated random-dot stereograms have been theorised based on animal models from invasive studies, but have not been experimentally verified. In this study, we employed a phase-consistent, temporally modulated alternating depth stereogram stimulus, where we created anticorrelation by inverting the contrast between the eyes. We recorded the electrical response of the resulting brain oscillations of our four participants using EEG in both the correlated and anticorrelated conditions. Our analysis found that the correlated stereograms elicited a strong coherency at the even harmonics of the depth alternation, and the anticorrelated stimulus created lower coherency peaks at the first harmonic of the depth alternation. While both conditions created a diminishment of spectral power in the beta band, we found that the anticorrelated condition created increased spectral power in the alpha band. Based on our findings, we have experimentally verified the presence of a neural mechanism triggered by anticorrelated random-dot stereograms in the human brain with our coherency analysis, and we are unable to explain the presence of alpha oscillations for this condition.